2019
DOI: 10.3390/cancers11030396
|View full text |Cite
|
Sign up to set email alerts
|

Limited Sensitivity of Circulating Tumor DNA Detection by Droplet Digital PCR in Non-Metastatic Operable Gastric Cancer Patients

Abstract: This study was designed to monitor circulating tumor DNA (ctDNA) levels during perioperative chemotherapy in patients with non-metastatic gastric adenocarcinoma. Plasma samples were prospectively collected in patients undergoing perioperative chemotherapy for non-metastatic gastric adenocarcinoma (excluding T1N0) prior to the initiation of perioperative chemotherapy, before and after surgery (NCT02220556). In each patient, mutations retrieved by targeted next-generation sequencing (NGS) on tumor samples were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…A key challenge of liquid biopsy approaches has been developing methods to detect and characterize small amounts of ctDNA in large populations of cell-free DNA (cfDNA). A variety of studies have focused on changes in ctDNA during the course of therapy, but mostly in the setting of metastatic disease and largely centered on the analysis of a limited number of genomic positions that may only represent a subset of clones of the tumor [20][21][22][23][24][25][26][27][28] . More recent studies have used panels of commonly mutated driver genes to allow detection of multiple driver clones, typically at the time of diagnosis, after surgery, or at disease progression 16,18,27,[29][30][31][32][33][34] .…”
mentioning
confidence: 99%
“…A key challenge of liquid biopsy approaches has been developing methods to detect and characterize small amounts of ctDNA in large populations of cell-free DNA (cfDNA). A variety of studies have focused on changes in ctDNA during the course of therapy, but mostly in the setting of metastatic disease and largely centered on the analysis of a limited number of genomic positions that may only represent a subset of clones of the tumor [20][21][22][23][24][25][26][27][28] . More recent studies have used panels of commonly mutated driver genes to allow detection of multiple driver clones, typically at the time of diagnosis, after surgery, or at disease progression 16,18,27,[29][30][31][32][33][34] .…”
mentioning
confidence: 99%
“…Circulating HPV DNA: A specific Form of ctDNA Numerous applications of ctDNA as diagnostic and predictive/ prognostic marker in oncology are under development (65)(66)(67). In most models, ctDNA is detected via the presence of somatic mutations, but the low rate of target molecules, especially in early stage tumors, implies that their detection can be affected by stochastic sampling leading to a lack of target molecules in some specimens (68), a limitation for clinical applications, (69). In this context, HPV-associated tumors represent a privileged model for the detection of ctDNA.…”
Section: Hpv Genome: a Tumor Marker For The Detection Of Ctdnamentioning
confidence: 99%
“…ctDNA could serve as a serological screening test, but the correlation between ctDNA detection and early-stage gastric cancers is unclear. An analysis of 20 patients with non-metastatic gastric cancer demonstrated that only 4 had detectable ctDNA at baseline [40]. The CancerSeek platform, combining ctDNA detection with protein biomarkers, reported improved sensitivity rates of 73 and 70% in non-metastatic gastric and oesophageal cancers, suggesting one strategy to improve detection [8].…”
Section: Upper Gastrointestinal Cancermentioning
confidence: 99%